E-Learning dalam Kajian Pendidikan Agama Islam di Perguruan Tinggi pada Abad ke-21 - Ulya, Vita Fitriatul; Abidin, Zainal (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
The 21st century learning paradigm has undergone a significant shift, demanding active participation from both educators and students in technology-based learning processes. This holds for the study of Islamic Religious Education (IRE), a mandatory component of the higher education curriculum. This literature research aims to highlight the urgency of leveraging e-learning in higher education for the study of IRE as a response to the challenges of the 21st century. The methodology employed in this study is literature research, examining 31 articles published in the last 5 years related to e-learning, IRE studies, and the learning paradigms of the 21st century. The research findings indicate the importance of e-learning in the study of IRE, providing students with learning experiences through digitalization and technology. Several learning management systems (LMS) are reviewed in this paper, such as Zoom Cloud Meeting, Google Classroom, Moodle, and Schoology. Through the features offered by these platforms, educators can innovate in managing digital-based learning, facilitating students' access to IRE learning materials, encouraging discipline in assignment submission, and enabling independent learning without constraints of space and time.